Vivência das sexualidades: o que dizem pessoas com deficiência intelectual? - Marcolino, Alinne Beserra de Lucena (2019)
Introduction: Society still deals in a prejudiced way with the sexuality of people with disabilities due to the fact that there are ―differences‖ in relation to the defining patterns of normality, thereby making this discussion relevant to the construction of new approaches with this matter. Objective: To analyze the way in which the experience of the sexualities of people with intellectual disabilities is configured. Methodological Path: This is a descriptive study with a qualitative approach that uses Gagnon's theory of sexual scripts as a theoretical reference which was attended by 16 people with intellectual disabilities, who were classified by the International Code of Diseases (ICD-10)/F-70.1 as people with mild intellectual disability degree. We used the semi-structured interview technique as a resource for collecting data. The corpus resulting from the interviews was processed by IRaMuTeQ software and analyzed through Descending Hierarchical Classification, Content Analysis and Word Cloud. The research project was approved by the Research Ethics Committee of the Center for Health Sciences of the Federal University of Paraíba, according to CAAE protocol 59410216.4.0000.5188. Results: We raised five classes of contents related to the sexuality of people with intellectual disabilities: ―meanings attributed to sexuality‖, ―care and protection‖, ―social and emotional support‖, ―dialogic barriers‖ and ―information sources‖. Sexuality was mentioned in body interactions, involving fondness, love, affection and commitment to the other. Moreover, it was exclusively pointed out as a way of expressing desires and pleasures. We identified the occurrence of dating relationships, consented by adults, almost always without a condom, using contraceptive pills as a contraceptive method. Dialogue with family members is still insufficient, faulty and/or inaccurate, and access to information on sexuality is superficial, coming from the internet and television. Final considerations: The sexuality of people with intellectual disabilities is very similar to the sexuality of others with respect to the expression of erotic desires and exposure to social standards. We evidenced normalized, regulated and controlling cultural permanencies that influence not only the interpersonal scripts, but also the intrapsychic scripts. Educational strategies should be adopted, including family members, educators and people with intellectual disabilities, where personalized support systems, devoid of repression, guilt and medicalization of behaviors, may help them to fully experience their sexualities.